Sixteen Years of Speckle Interferometry at the WIYN Observatory - Van Altena, Wm. F.; Horch, Elliott; Casetti-Dinescu, Dana I. (American Astronomical Society, 2017)
Speckle interferometry at Yale started in 1994 with a three-year program of observations at the Yale Southern Observatory at El Leoncito, Argentina. After this experience, we began a long-term program of speckle observations at the WIYN 3.5-m telescope at Kitt Peak National Observatory, first using a MAMA detector, then CCD and finally EMCCD technology. We describe the evolution of the program, its main results in terms of discovered components, orbital parameters and masses. While the Yale program ended in 2013, it provided the springboard for continued speckle efforts at WIYN, the Discovery Channel 4.3-m Telescope, and the Gemini 8.1-m Telescopes for binary star research, exoplanet science, and other projects. An important outcome of this research will be the incorporation of the soon to be released high-precision Gaia parallaxes into our observations.